2016
DOI: 10.1371/journal.pone.0163853
|View full text |Cite
|
Sign up to set email alerts
|

Less Empathic and More Reactive: The Different Impact of Childhood Maltreatment on Facial Mimicry and Vagal Regulation

Abstract: Facial mimicry and vagal regulation represent two crucial physiological responses to others’ facial expressions of emotions. Facial mimicry, defined as the automatic, rapid and congruent electromyographic activation to others’ facial expressions, is implicated in empathy, emotional reciprocity and emotions recognition. Vagal regulation, quantified by the computation of Respiratory Sinus Arrhythmia (RSA), exemplifies the autonomic adaptation to contingent social cues. Although it has been demonstrated that chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 48 publications
(65 reference statements)
2
27
0
1
Order By: Relevance
“…Further studies should explore whether dysfunctional family environments impact infants’ facial responses to others’ emotional action kinematics. Recently, it has been shown that childhood maltreatment affects facial responses to emotional facial expressions (Ardizzi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies should explore whether dysfunctional family environments impact infants’ facial responses to others’ emotional action kinematics. Recently, it has been shown that childhood maltreatment affects facial responses to emotional facial expressions (Ardizzi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we studied the potential increment in cardiac synchrony among spectators of the same live performances and how this spontaneous physiological synchrony could be related to spectators individual rating of performance emotional intensity. Among the different levels at which synchrony can occur, cardiac synchrony is our primary candidate to be investigated, because autonomic responses are key substrates of emotional experience [30][31][32] . Moreover, spontanous autonomic reactions are extremely common in responses to art [33][34][35] .…”
mentioning
confidence: 99%
“…Zahn-Waxler et al, 1995) or a mixture of joyous/sad stimuli (e.g. Ardizzi et al, 2016). Although it is important to consider the nature of the emotion elicited in the current study, the emotional valence of the task stimuli has not been shown to influence the pattern of findings observed in previous studies.…”
Section: Future Directionsmentioning
confidence: 72%
“…The literature examining the relation between empathy and autonomic nervous system reactivity reveals a range of findings. The majority of these studies, however, found that increased empathy was associated with increased sympathetic or decreased parasympathetic activity in response to stressful or emotionally-provocative stimuli (Ardizzi et al, 2016;Balconi & Bortolotti, 2012;de Wied, et al, 2012;Geringer, 2015;Liew et al, 2011;Miller, et al, 2016;Oliveira-Silva & Gonclaves, 2011;Tracy & Giummarra, 2017;Truzzi et al, 2016;Wiesenfeld et al, 1984;Zahn-Waxler et al, 1995). The series of studies conducted by Stellar and colleagues (2015), in contrast, found that engagement in compassion was associated with decreased sympathetic response to stress.…”
Section: Development Andmentioning
confidence: 99%
See 1 more Smart Citation